Childbirth experience in women at high risk in facing the delivery process at UGM academic hospital - Evita Ratih Dewayani (Academic Hospital Journal, 2021)
Background: High-risk pregnancy is a severe threat to the health and life of pregnant women and babies, considering that this can increase the risk of complications during pregnancy, childbirth and puerperium. About 20 million women worldwide have high-risk pregnancies, and it is known that more than 800 die each day. Pregnant women have potential risks during pregnancy, childbirth and the puerperium. The mother's lack of knowledge about pregnancy health problems and health service providers can increase inappropriate handling risk by health workers. So, women should understand the concept of high-risk pregnancies to reduce these risks. Research Objectives: To determine the childbirth experiences in mothers at high risk in the delivery process at UGM Academic Hospital. Method: Qualitative Research with Descriptive-Narrative Design. Results: The mothers knew the risks of pregnancy, but they were less aware of the risks of other pregnancies. Mothers’ experience in choosing a place of delivery was influenced by personal experiences, family, friends, or other people. The availability of adequate hospital facilities, service flow, and ownership of insurance coverage were also other factors in choosing a maternity hospital. Conclusion: Mothers are aware of the risks of pregnancy, but they are less aware of other pregnancy risks. Suggestion: Mothers should be aware of the risks of pregnancy and need to learn more about other pregnancy risks. It is hoped that they will be better prepared if a high-risk pregnancy occurs.